Formation of corporate strategy by the enterprise engaged in foreign economic activity - Mukan, O.; Hanas, L.; Tsyb, Y. (Lviv Politechnic Publishing House, 2018)
The article proves the importance of corporate strategy formation and the significance of considering the current state of the economy by the enterprise engaged in foreign economic activity. The nature of the corporate strategy, as well as stages and principles of its creation are analyzed. Based on the analysis of domestic and foreign scientific developments, the definition of the concept “corporate strategy” is provided. The process of the corporate strategy formation is also considered. The principles of the corporate strategy formation are systematized and their short description is presented. Requirements for the corporate strategy formation are developed.
Keywords: corporate strategy; enterprise; strategic directions; principles; business unit; strategic planning; 338.1; 339.976.2